Two new genera of Nearctic Chamaemyiidae (Diptera: Lauxanioidea) associated with Cinara aphids (Hemiptera: Aphididae) on Pinus - Gaimari, Stephen D. (Zootaxa, 2020)
Two new genera of Chamaemyiidae (Diptera: Lauxanioidea) are described and illustrated, including: Chamaethrix gen. nov. (type species Chamaethrix necopina sp. nov.), possibly a predator of Cinara ponderosae (Williams) on Pinus ponderosa in the southwestern United States; and Vitaleucopis gen. nov. (type species Vitaleucopis nidolkah sp. nov.; other included species Vitaleucopis astonea (McAlpine), comb. nov., and Vitaleucopis scopulus sp. nov.), predators of Cinara aphids and possibly adelgids on Pinaceae in western North America. Immature stages are discussed or described and illustrated for some taxa, including the eggs of Chamaethrix necopina and Vitaleucopis nidolkah; and the third instars and puparia of Vitaleucopis nidolkah.